Pengaruh risiko pasar dan tingkat kecukupan modal terhadap profitabilitas pada bank BNI periode 2013 – 2020 - Lidia Noer Khoeriah; Gusganda Suria Manda (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2021)
In the banking industry, every company always try to avoid risk, both inside and outside of the organization business entity. The purpose of this study was to determine whether the bank's market risk (NIM) and capital adequacy ratio (CAR) BNI from 2013 to 2020 had a simultaneous or partial effect on profitability (ROA). The type of this study is quantitative study. The population in this study is BNI’s quarterly financial reports from 2013 to 2020. Up to 30 study samples were obtained. The analysis technique used in this study is multiple linear regression analysis with the help of the IBM SPSS Statistics 25 program. The results showed that: (1) Simultaneously, market risk (NIM) and the level of capital adequacy ratio (CAR) have a significant effect on profitability (ROA), (2) Partially, the results on the market risk variable (NIM) have a significant effect and have a positive relationship on profitability (ROA), (3) Partially, the results on the variable level of capital adequacy ratio (CAR) have a significant effect and have a positive relationship to profitability (ROA).